Magnetoresistance Features at the Magnetic Field-Induced Phase Transition in FeRh Thin Films - Aleksei S. Komlev; Rodion A. Makarin; Viktoria E. Maltseva; Vladimir I. Zverev; Alexey S. Volegov; Nikolai S. Perov (Directorate for Research and Community Services (LPPM) ITB, 2023)
The causes of the appearance of first-order magnetic phase transitions remain a mystery. FeRh alloy is a classical material where a first-order magnetic phase transition occurs. The authors of this article studied the phase transition from the antiferromagnetic state to the ferromagnetic state in FeRh alloy. Comparison of the magnetometry and transport properties results allowed us to determine a number of differences in the mechanisms of the phase evolution during magnetic field and temperature induced transition. This article notes the priority of the rearrangement of the micromagnetic structure of the ferromagnetic phase as a result of the induction of a phase transition by a magnetic field. The main feature of the magnetic field induced phase transition compared to the temperature induced one is the change in the micromagnetic structure of the ferromagnetic phase. The growth of a ferromagnetic phase with less scattering fields leads to asymmetric behavior when a phase transition is induced near the metastable state. We also focused on the importance of taking into account the effect of magnetostriction when analyzing the evolution of the phase transition, which leads to the irreversibility of the phase transition near a zero magnetic field.